Constitutional and Administrative Law in Nigeria: Are They Instruments of Governance? - Adegbami, Adeleke; Ganiyu, Akeem Adewale (Public Governance, Administration and Finances Law Review, 2023)
Are constitutional and administrative laws in operation in the institutions and agencies of government in Nigeria? How effective are these laws at regulating the activities of the government in the country? Has the law enhanced the quality of services delivered by the government? What are the factors influencing the practice of public administration in Nigeria? Are these factors in consonance with administrative law? These are germane questions to which this study attempted to provide answers. It relies on secondary data, which were subjected to content analysis. The study argues that the 1999 Constitution of Nigeria, prepared by the government without legitimacy (the military), and handed over to the civilian administration some twenty-three years ago, with little or minor amendment to date, made the legitimacy of the government of Nigeria’s Fourth Republic questionable. And, apart from the faulty preparation of the constitution and some amendments made to it by the National Assembly, the elite, who appear to be above the law, do not allow the constitution to work. These elite are mainly among the legislature, the judiciary and the executive; they are all guilty of stemming and whittling down the power of the constitution, and the law of administration by their flagrant disregard for the rule of law and the constitution in their various capacities. This study therefore, concludes that, until Nigeria’s constitution is redrafted, and constitutional law and administrative law properly applied, quality or good governance will continue to elude the country.